Preventing long-term disability in CIDP: the role of timely diagnosis and treatment monitoring in a multicenter CIDP cohort - Quint, Paula; Schroeter, Christina B; Kohle, Felix; Öztürk, Menekse; Meisel, Andreas; Tamburrino, Giuliano; Mausberg, Anne K; Szepanowski, Fabian; Afzali, Ali Maisam; Fischer, Katinka; Nelke, Christopher; Räuber, Saskia; et al. (Journal of neurology, 2024)
BACKGROUND: Chronic inflammatory demyelinating polyneuropathy (CIDP) is an inflammatory disease affecting the peripheral nerves and the most frequent autoimmune polyneuropathy. Given the lack of established biomarkers or risk factors for the development of CIDP and patients' treatment response, this research effort seeks to identify potential clinical factors that may influence disease progression and overall treatment efficacy. METHODS: In this multicenter, retrospective analysis, we have screened 197 CIDP patients who presented to the University Hospitals in Düsseldorf, Berlin, Cologne, Essen, Magdeburg and Munich between 2018 and 2022. We utilized the respective hospital information system and examined baseline data with clinical examination, medical letters, laboratory results, antibody status, nerve conduction studies, imaging and biopsy findings. Aside from clinical baseline data, we analyzed treatment outcomes using the Standard of Care (SOC) definition, as well as a comparison of an early (within the first 12 months after manifestation) versus late (more than 12 months after manifestation) onset of therapy. RESULTS: In terms of treatment, most patients received intravenous immunoglobulin (56%) or prednisolone (39%) as their first therapy. Patients who started their initial treatment later experienced a worsening disease course, as reflected by a significant deterioration in their Inflammatory Neuropathy Cause and Treatment (INCAT) leg disability score. SOC-refractory patients had worse clinical outcomes than SOC-responders. Associated factors for SOC-refractory status included the presence of fatigue as a symptom and alcohol dependence. CONCLUSION: Timely diagnosis, prompt initiation of treatment and careful monitoring of treatment response are essential for the prevention of long-term disability in CIDP and suggest a "hit hard and early" treatment paradigm.
Keywords: senioři; Disease Progression; Retrospective Studies; progrese nemoci; Cohort Studies; intravenózní imunoglobuliny; Middle Aged; mužské pohlaví; Adult; Immunoglobulins, Intravenous; kohortové studie; prednisolon; ženské pohlaví; retrospektivní studie; Humans; lidé středního věku; chronická zánětlivá demyelinizační polyneuropatie; Polyradiculoneuropathy, Chronic Inflammatory Demyelinating; Prednisolone; dospělí; Female; Aged; lidé; Male